First-generation paclitaxel- vs. second-generation zotarolimus-eluting stents in small coronary arteries: the BASKET-SMALL Pilot Study - Raban Jeger; Matthias Pfisterer; Otmar Pfister; Peter Rickenbacher; Michael Handke; Nicole Gilgen; Michael Coslovsky; Christoph Kaiser (Advances in Interventional Cardiology, 2016)
Introduction : Event rates after percutaneous coronary interventions (PCI) are higher in small than large coronary vessels but may vary between different drug-eluting stent (DES) types. Aim : To assess the efficacy of two different DES in small vessel disease. Material and methods : Patients with small vessel PCI were randomised 1 : 1 to a first-generation paclitaxel- vs. a second-generation zotarolimus-eluting stent. The primary endpoint was a composite of cardiac death, non-fatal myocardial infarction, and target vessel revascularisation after 2 years. Results: Overall, 191 patients were enrolled: 100 with a paclitaxel- and 91 with a zotarolimus-eluting stent. Baseline characteristics were similar in both groups. After 2 years, rates of the primary endpoint were numerically higher for zotarolimus- than paclitaxel-eluting stents (9.9% vs. 5.0%, hazard ratio 2.09, 95% confidence interval (CI) 0.7–6.2, p = 0.19), which was mainly driven by higher rates of target vessel revascularisation (6.6% vs. 2.0%, hazard ratio 3.39, 95% CI: 0.68–16.78, p = 0.14). Based on this, a total of 1,019 patients would be necessary to demonstrate at least non-inferiority between the DES used. Conclusions : In this pilot study, paclitaxel-eluting stents had a favourable efficacy profile in small vessel disease, although the numbers were too small to draw final conclusions. Based on the prohibitively high sample size for a randomized controlled trial between DES, other treatment options should be considered.